Anal tuberculosis complicating anti-TNFα therapy - Luquín, Nuria (BMJ Case Rep, 2014)
A 42-year-old man receiving anti-tumour necrosis factor α (anti-TNFα) therapy with adalimumab due to psoriatic arthritis presented with a 2-month-old anal ulcer. An apical right lung infiltrate was found in his chest X-ray, although he had no pulmonary symptoms. Two biopsies of the ulcer were taken and reported as granulomatous, necrotising, with chronic inflammation (first), and as hyperplasic epidermis with linfocitary infiltrate and the presence of plenty of plasmatic cells (second). Histochemical techniques, including Ziehl-Neelsen, Grocott and periodic acid-Schiff stains, and PCR for Mycobacterium tuberculosis on both biopsies were negative. Serology for HIV, syphilis and hepatitis were also negative. In the second biopsy culture, moderate colonies of M. tuberculosis finally grew. The patient started a four-drug antituberculosis regimen. Adalimumab was discontinued and etanercept introduced after 2 months of antituberculosis therapy. The patient remained on therapy for 9 months with complete ulcer resolution.